PRONUNCIATION ERRORS BY NHK WORLD TV NEWSLINE REPORTERS - SANJAYA, ALFIAN EKA PUTRA ADI (Fakultas Ilmu Budaya Universitas Brawijaya, 2014)
Keywords: NHK WORLD, Newsline, Pronunciation, Error Analysis. NHK WORLD is a Japanese International broadcasting media whose jobs is to give information of Japan to the world. Interestingly, the reporters of international levels of the media committed some errors on their pronunciation. Thus, there are two objectives to achieve in this research, (1) to identify the errors of pronunciation in vowels and consonants and (2) to identify the possible causes of the pronunciation errors in vowels and consonants that are made by NHK WORLD TV Newsline Reporters.This study used a descriptive qualitative approach and document analysis to analyze five video of the five speakers which were downloaded from the NHK WORLD website. Further, the writer used the surface strategy taxonomies by Dulay,et al. (1982) in identifying the errors and Saville-Troike (2006) theory of interference of the first language and differences in learners to identify the possible causes of the pronunciation error.The result in this study found that in vowels, there are 20 kinds of substitution, 6 kinds of addition and 1 omission and the vowel errors committed mostly are the substitution of vowel /É/ to /a/ that reaches 10 errors. Meanwhile, the consonant errors have 11 kinds of substitution, 4 kinds of omission and 1 addition and the error committed mostly is the substitution of /l/ to /r/ which has a total of 10 errors. Moreover, the writer elaborates two possible causes of errors made by the reporters which the first is the Japanese language characteristic and the second is the aptitudes of the learner. In conclusion, this study has proven that Japanese reporters have difficulties in pronouncing English vowels rather than the consonant, and the interference of the first language is the possible reason of committing errors.The writer suggests the next writerÂ use other subjects from other countries or other media. Moreover, the next writer can also use the same subjects with the concern of gender in language learning.